Mahabbah Kepada Allah Dalam Al-Qur’an - Ulfatun Naimah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This research discusses about mahabbah to Allah. By using the thematic interpretation method, the results of the study conclude that mahabbah to Allah is love to Allah SWT. The Qur'an emphasizes that love of Allah must follow the Prophet Muhammad. A love statement that is not accompanied by obedience to the Prophet Muhammad. or not accompanied by obedience to the Shari'ah, only false love that is limited to words. Love is divided into three, namely the love of ordinary people, the love of the wise and the love of the wise. Meanwhile, Ibn Arabi interprets love for Allah even deeper than stated in the terms in the Qur'an. He often expresses some of his feelings about love for God which are deep and difficult to digest by the general public.